Legal Analysis Of Violence By Prisoners In State Detention House Class I Medan In Normative Legal Perspective - Jamillah Jamillah (International Asia Of Law and Money Laundering (IAML), 2023)
The purpose of writing this article is to explain the forms and consequences of violence by prisoners in State Prison Class I Medan, the factors that cause violence by prisoners in State Prison Class I Medan, and efforts to overcome cases of violence by prisoners in State Prison Class I Medan . To obtain data in the writing of this article, research is carried out, to obtain secondary data is carried out by reading legislation, scientific papers, opinions of scholars, books, articles and other materials related to this research, and field research is carried out to obtain primary data related to this research through interviews with respondents and informants in this writing. Based on the results of the study, it is known that the form and consequences of violence by prisoners in Class I Detention Center Medan is in the form of misdemeanor and ordinary abuse which resulted in the victim being seriously injured and minor injuries and the perpetrator received a punishment in the form of confinement in isolation. The factors that cause violence by prisoners in Class I Detention Center Medan are individual problems, personal grudges, inadequate room capacity, and the absence of familiarity and harmonious relationships between fellow inmates. Efforts to overcome cases of violence by prisoners in Class I Detention Center Medan is given sanctions in the form of reprimands, put in isolation and not given remission, security units supervise each room of prisoners, this supervision is carried out for 1x24 hours, besides that each block is guarded by a public picket, which is tasked with guarding prisoners and ensuring that there is no disturbance of order in Class IIB Detention Center Banda Aceh. It is recommended to Rutan Klas IIB Banda Aceh to increase the number of detention rooms, so that in one room inmates do not overcapacity, counseling guidance, it is expected that surveillance efforts carried out by the security unit of Rutan Klas I Medan are divided into 3 teams plus 4 teams, this addition is intended that at 6 pm to 7 AM can be divided into 2 teams at 6 pm to 12 pm and 12 pm to 7 am.